Cost comparison studies of fisherman boat for wood and fiberglass material - Mohd. Solahuddin, Abdullah (2008)
This thesis presents the designing and analysis of cost estimation between wood and fibreglass material. This thesis also contains loading analysis that applied at boat hull. The designing will involve the characteristic of flexible boat that have durability and can use in any condition at the shore environment. The materials that will use in built this boat also need to consider for high resistant. Furthermore, the environment of shore will make any accident and this design needs to prevent boat from broke —up from floating wood, coral and anything at the shore. The loading of fish and their other load can make boat sink, so this problem need to be analyze probably in this thesis to get the great design that can withstand a lot of load. Result from analysis showed that this design can with stand with 2400N that applied at the boat hull and this boat also have a special characteristic such as it can move faster in wave, stable and safe from seawater enter in the boat.